Optimizing Da'wah Management Through Social Media in the Millennial Era at BMT Bina Ummah - Suwoto, Nur Salim; Zen, Muhammad (Institut Agama Islam Negeri Parepare, 2023)
This study aims to determine the optimization of BMT Bina Ummah missionary management through social media in the millennial era. This research is a field research by observing people interact and trying to understand it. Data collection is done by interviews, observation, documentation. The primary and secondary data sources collected were then processed using descriptive analysis methods with a qualitative approach. The results of this study are optimizing the management of da'wah by BMT Bina Ummah in managing its da'wah in the millennial era by creating interesting and easy-to-understand content on social media